2011
DOI: 10.1534/genetics.111.133660
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Elevated Germline Mutation Accumulation Under Oxidative Stress in Caenorhabditis elegans

Abstract: Variation in rates of molecular evolution has been attributed to numerous, interrelated causes, including metabolic rate, body size, and generation time. Speculation concerning the influence of metabolic rate on rates of evolution often invokes the putative mutagenic effects of oxidative stress. To isolate the effects of oxidative stress on the germline from the effects of metabolic rate, generation time, and other factors, we allowed mutations to accumulate under relaxed selection for 125 generations in two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 93 publications
(148 reference statements)
2
27
0
Order By: Relevance
“…One potential issue is that mutation-rate estimates are almost always obtained under optimal laboratory growth conditions, raising questions as to whether harsher environmental conditions would result in lower (or higher) levels of replication fidelity. Experimental work in this area has led to mixed results (31)(32)(33), and there is considerable room for further research.…”
Section: Discussionmentioning
confidence: 99%
“…One potential issue is that mutation-rate estimates are almost always obtained under optimal laboratory growth conditions, raising questions as to whether harsher environmental conditions would result in lower (or higher) levels of replication fidelity. Experimental work in this area has led to mixed results (31)(32)(33), and there is considerable room for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, temperature effects on mutation rate may not be mediated by metabolic rate, but by other processes (e.g. In any case, the proposed mechanism by which metabolic rate may affect mutation rate, namely ROS production, appears to be absent in mammalian cells (Hoffmann et al, 2004) and the nematode Caenorhabditis elegans (Maupas) (Joyner-Matos et al, 2011). In addition, direct tests for associations between RMR and the rates of mutation or molecular evolution have usually produced nonsignificant results (Mooers & Harvey, 1994;Bromham, Rambaut & Harvey, 1996;Gissi et al, 2000;Lanfear et al, 2007;McGaughran & Holland, 2010;Feng et al, 2014).…”
Section: (6) Rates Of Mutation and Molecular Evolutionmentioning
confidence: 99%
“…Furthermore, although correlative evidence for the metabolic rate hypothesis in animals is mixed [24][25][26] , experiments in animals have shown that oxygen radicals generated in organelles do not damage the nuclear DNA of the same cell 27 , and that germ-line mutations do not accumulate under increased oxidative stress 28 . If the same is true for plants, the metabolic rate hypothesis cannot explain the link we have observed between height and rates of molecular evolution in the nuclear genome.…”
Section: Article Nature Communications | Doi: 101038/ncomms2836mentioning
confidence: 99%